Mycotoxins in aquaculture: feed and food. (10th November 2018) - Gonçalves, Rui A.; Schatzmayr, Dian; Albalat, Amaya; Mackenzie, Simon
Abstract: Mycotoxins, secondary metabolites produced by moulds, are responsible for causing significant economic losses due to spoilage of agricultural products but also due to direct or indirect health impact on livestock upon ingestion of mycotoxin contaminated feedstuffs. Aquaculture farmed species are not an exception and studies reporting mycotoxin‐related issues in the aquaculture industry have been increasing. However, our understanding on the prevalence and impact of mycotoxins in the aquaculture sector is still lower compared to the terrestrial livestock sector. Consequently, regulatory limits and guidance values have been defined based on the studies on terrestrial farm animals. The aim of this review is to compile and critically assess mycotoxin occurrence and co‐occurrence in aquaculture finished feeds, and understand the risk of mycotoxin carry‐over in aquaculture seafood products. Furthermore, we aim with this review to raise awareness to the scientific community, the regulatory authorities and the aquaculture industry to the need for specific aquaculture mycotoxin maximum concentration levels for both aquaculture feeds and foods.